Blood Pressure Responses in Isokinetic Dynamometry Test in Elderly Community Women: An Exploratory Study - Rubens Vinícius Letieri; Guilherme Eustáquio Furtado; Taís Rieping; Mayrhon José Abrantes Farias; Ana Maria Miranda Botelho Teixeira (Desafio Singular, 2018)
The aim of the study was to verify the systolic, diastolic and mean arterial pressure response in elderly women during isokinetic test. The study included 54 females (68.8 ± 5.9 years) divided into two age groups (Group 1: 60 to 70 and group 2: above 71 years). BP was measured before and immediately after the isokinetic knee extension / flexion test in the concentric-concentric mode. After the test, significant elevations were observed in relation to the pre-test in SBP (G1: Δ% = 29.7%, G2: Δ% = 20.6%, p <.01, respectively) and in MAP (G1: Δ% = 7.6 %, G2: Δ% = 8.4%, p <.01, respectively). The use of isokinetic tests produces elevations in systolic blood pressure and mean arterial pressure in elderly women. Increases occur independently of the age group studied. However, the increases detected do not appear to be of sufficient magnitude to constitute a health hazard whereby isokinetic tests can be safely applied in this population.